ЕЛЕКТРОМЕХАНІЧНІ ТЯГОВІ ХАРАКТЕРИСТИКИ КОАКСІАЛЬНО-ЛІНІЙНОГО ДВИГУНА З ПОСТІЙНИМИ МАГНІТАМИ ТА МАГНІТНИМ ПІДВІСОМ - Голенков, Г.М.; Пархоменко, Д.І. (Інститут електродинаміки НАН України, Київ, 2014)
The methods of vibratory building products driving in ground with vibratotors are known. The coaxial-linear motor with constant magnets and magnetic bracket is used as a drive of these vibratotors. The moving element of this motor makes axial mechanical vibrations with frequency of current in energizing coil. We can influence on regulation of amplitude of mechanical oscillation with current strength and direction of direct current. The methods of computer modeling and experimental investigations of electromechanical propulsion performance characteristics of these motors. The computer modeling and experimental investigations are made for specified position of secondary cell and values of current strength in energizing coil of motor. During the investigations the dependences of propulsion performance characteristic in motor from relatively attitude position of secondary cell and values of current strength in energizing coil are presented. References 7, figures 6.